Pengaruh Teori Kewirausahaan Terhadap Keberhasilan Usaha di Era Digital Dalam Novel #GIRLBOSS Karya Sophia Amoruso - Herlina Sari Indri Astuti; Mayang Sari; Eva Dwi Kurniawan (CEMERLANG : Jurnal Manajemen dan Ekonomi Bisnis, 2024)
The millennial generation is a generation that has creative ideas or innovations. As a business person or entrepreneur, a person must have knowledge and skills in entrepreneurship, especially in the digital era like now. This research was conducted with the aim of finding out and revealing what abilities or theories are used by millennial generation business actors in New York City. The literary work used as a source of research data is the novel entitled #GIRLBOSS by Sophia Amoruso. This research is a type of qualitative descriptive research using the heruistic method, namely reading thoroughly and the hermeneutic method, namely the study of text interpretation or the process of interpreting text. The results of this research are that there are 3 theories of entrepreneurship which include economic theory (taking advantage of opportunities that can create innovation), psychological theory (what underlies business) and behavioral theory (skills in managing and advancing business).